STATE ADMINISTRATION IN THE EPOCH OF Т.УСУБАЛИЕВА AND PRESENTLY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article author conducted a comparative analysis: common and specific in state administration in the epoch of T Usubalievand presently.
Keywords: Management, T Usubaliev, Supreme Soviet, Жогорку Кенеш, Folk Commissariat, ministry, public organ, shots of and other.